Kontribusi Kebiasaan Belajar terhadap Motivasi Berprestasi Siswa serta Implikasinya dalam Pelayanan Bimbingan dan Konseling - Maria Oktasari (Program Studi Bimbingan dan Konseling FKIP UMSU, 2019)
The purpose of the study was to determine the contribution of learning habits to student achievement motivation. The research method uses quantitative methods. The population of this study includes all students of class X, XI, and XII of SMA Master Depok, who are enrolled in the 2017-2018 academic year as many as 105 students. The research sample was taken using saturated sampling technique so that the sample was 105 people. Hypothesis testing in research uses simple regression analysis. The results showed that learning habits contribute to student achievement motivation.